Determining the COVID-19 Knowledge, Awareness and Anxiety Levels of Intern Dentists - Akbulut, Yasemin; Onder, Merve; Kutlu, Gamze; Durur, Fatih; Orhan, Kaan (International Journal of Occupational Safety and Health, 2023)
Introduction: COVID-19 is a contagious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The nature of dentistry leads to close contact with patients and exposure to saliva, blood, and other bodily fluids during treatment processes and it is a field where high-frequency devices that can make it easier for virus contamination are used. This study aims to determine the knowledge and approaches of COVID-19 infection control of intern dentists who have begun face-to-face education and their COVID-19-related fear and anxiety levels. Methods: The study comprised 4th and 5th-year students who began face-to-face education at the Ankara University Faculty of Dentistry 2020/2021 spring semester. A questionnaire was used as the data collection tool for this study. The data were collected using a knowledge questionnaire and a COVID-19 fear and anxiety scale. Results: The average COVID-19 knowledge score of the students was 63.65±9.64, their coronavirus fear average score was 17.63±5.57, and their anxiety average score was found to be 2.37±3.32. A positive relationship was found between the anxiety scores and the COVID-19 fear scores. The results of this study show that the COVID-19 knowledge level and fear of dentistry students are moderate and that their COVID-19 anxiety level is low. Conclusion: It was found that the knowledge and fear of coronavirus levels of intern dentistry students were moderate and that their coronavirus anxiety level was low.